Innovative Financing for Urban Rail in Indian Cities: Land-based Strategic Value Capture Mechanisms - Jillella, Satya Sai Kumar (Curtin University, 2017)
Emerging cities are seeking urban rail but have difficulty with funding. This research uses the Bangalore Metro rail to develop an innovative land-based ‘strategic value capture' (VC) financing system suitable for Indian cities and other emerging cities. It shows significant land value uplift that could be used for VC funding. The four frameworks and strategic interventions developed in this research are novel contributions in India and apply to other emerging cities as well.